PENGARUH PEMBERIAN SUMBER SERAT BERBEDA DALAM PAKAN TERHADAP KECERNAAN SEMU SERAT KASAR DAN HEMISELULOSA PADA AYAM PEDAGING STRAIN COBB - Sasae, Yasinta Y.A.; Londok, J.J.M.R.; Tulung, B.; Rahasia, C.A. (ZOOTEC, 2020)
THE EFFECT OF DIFFERENT FIBER SOURCES IN THE FEED TO DIGESTIBILITY OF CRUDE FIBER AND HEMICELLULOSE IN COBB STRAIN OF BROILERS. This research was carried out with the aim to determine the effect of providing different sources of fiber in feed on the apparent digestibility of crude fiber and hemicellulose in cobb strain of broilers. This study used 20 cobb strain of broilers 35-day-old. The design used was a Completely Randomized Design (CRD) with the treatment of 4 different fiber sources in the feed which was repeated 5 times. The treatments consisted of: R0 (commercial feed),R1 (commercial feed with coffe skin), R2 (commercial feed with rice bran), R3 (commercial feed with coconut pilp). Variables measured were: apparent digestibility of crude fiber and hemicellulose. Apparent-digestibility measurements using the total collection method. Data were analyzed using general linear model (MINITAB version 16), then differences between treatments were tested with Tukeyâ€™s simultaneous test. Apparent digestibility of crude fiber feed has a very different (P<0,01) with treatment R2 and R1. The treatment of R2 was not significantly different (P>0,05) from R1. Apparent digestibility test for hemicellulose shows that R3 is the same asÂ  R0, but it is significantly different (P<0,01) with treatment R2 and R1. The treatment od R2 was not significantly different (P>0,05) from the treatment of R1. It was concluded that coconut pilp as a source of fiber in the feed of strain cobb of broilers provides better digestibility of coarse and hemicellulose fibers than coffe huks and coffe branKeywords: Apparent digestion of crude fiber, Apparent digestion of hemicellulose, strain cobb of broiler